Synthesis and characterization of novel cofacial bis-phthalocyanines containing 16-crown-5 ether groups - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
Four crown ether substituted cofacial bis-phthalocyanines were prepared by the cyclic condensation of dihydroxy groups of pentaerythritol moieties of phthalocyanine with tetraethyleneglycol ditosylate in the presence of NaH as base in refluxing THF. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: GAS-SENSING PROPERTIES; ZINC PHTHALOCYANINES; METAL-FREE; CROWN; 1,2-BIS(3,4-DICYANOPHENOXYMETHYL)BENZENE; DERIVATIVES; CLAMSHELL